Linking Women's Empowerment and their Resilience - Leder, S. (CGIAR Research Program on Water, Land and Ecosystems, 2016)
This literature review explores different conceptualizations of empowerment and possible links to resilience within gender and development studies. It takes theoretical perspectives of power and empowerment into account, reviews dimensions and relations influencing women's agency, and critically reflects on approaches for quantifying empowerment. Based on conceptualizations of empowerment ranging from narrow and instrumentalist to complex ones that engage with structural and social change, interpretations have diverse and reciprocal impacts on methodological considerations and the nature of empirical evidence. Furthermore, these diverse conceptualizations are used to evaluate and inform developmental policies and projects to varying degrees.